Pendidikan Karakter dalam Teks Cerita Anak Pada Buku Ajar Bahasa Indonesia di Sekolah Dasar sebagai Penguatan Profil Pelajar Pancasila - Siti Mukaromah; Farida Nugrahani; Benedictus Sudiyana (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This research aims to 1) Describe the characteristics of children's stories texs in Indonesian language textbooks in elementary schools based on intrinsic elements; 2) Describe the content of character education in children's stories texs in Indonesian language textbooks in elementary schools; and 3) Describe the strengthening of the profile of Pancasila students in children's stories texs in Indonesian language teaching books in elementary schools. he data is in the form of dialogue/narration excerpts containing character values ​​and strengthening the profile of Pancasila students. The data source is an Indonesian language textbook for Elementary School Classes IV and V, Ministry of Education and Culture, 2021. From all these stories, 4 story titles were taken purposively. Data was collected using document study techniques. Data analysis was carried out based on a literary sociology approach using the interactive analysis model from Miles & Hubberman. The results shown in this research are that children's stories in elementary school have characteristics, themes raised about cooperation, health, obeying parents' advice, and affection between friends. The storytelling style uses a third person point of view. The time setting generally occurs during the day, with a tense atmosphere, the setting varies. Stories contain an introduction, problem, and solution. Children's stories in Indonesian language textbooks in elementary schools contain character education values ​​which include: 1) nationalist; 2) religious; 3) integrity; 4) mutual cooperation; and 5) independent. The value of character education supports P5 in dimensions 1) having faith, being devoted to God Almighty and having noble character; 2) creative; 3) independent; 4) global diversity; 5) critical reasoning; and 6) mutual cooperation.